Development in video technology for coaching - Wilson, B. D. (Sports Technology, 2008)
The first section of this article contains a brief description of the video technology that is commonly used in coaching. Camcorders and digital video linked to computer capture and control provide inexpensive training tools for coaches. The rationale for the use of video in coaching is then presented from the perspective of a sports biomechanist. The objective is to enhance coach and athlete performance through a better understanding of all aspects of the athlete's performance. The use of video permits the coach to first focus on the coaching task with video providing additional tools for performance review. How we use the technology with examples of the application of video technology in sports is discussed in the next section of the article. For coaching, the emphasis is on qualitative uses of video for game analysis of technical skills, assessment and monitoring of technical skills, feedback in training, and reporting and presentation. Finally, areas of development are presented that will enhance the use of video in coaching (i.e. smart systems for movement analysis), real-time skill analysis and soft real-time auto-coding of performance. (This paper is based partly on the conference paper and book chapter Wilson BD, Pharmy A, Nadzrin M. Video technology and coaching. In: Fuss FK, Subic A, Ujihashi S (Eds.), The Impact of Technology on Sport II, pp. 897-904)